2022
DOI: 10.1002/admi.202200478
|View full text |Cite
|
Sign up to set email alerts
|

Toward Graphene‐Enhanced Spectroelectrochemical Sensors

Abstract: The SERS effect arises mainly from electromagnetic (EM) and chemical (CM) enhancement of the Raman signal. [3] The EM enhancement is on the order of ≈|E| 4 , amplifying signals >10 8 , where E is the intensity of the EM field. On the other hand, CM enhancement has been shown to enhance the signal ≈10-100×. Nevertheless, SERS enhancement is contingent on the quality of the substrate. Preparation of a suitable substrate requires rigorous micro/nanofabrication processes, such as electrochemical or high vacuum dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…7D (iii)) graphene in devising GR-enhanced spectro-electrochemical sensors (GE-SPECSs). 195 Their studies revealed that hole-doped h-graphene exhibited superior GERS signals compared to pgraphene, achieving a LOD of around 10 −7 M. By capitalizing on the adjustable work function of graphene, they demonstrated the ability to modulate the GERS signal and probe various oxidation states of molecules through the application of appropriate external potentials (Fig. 7D (i)).…”
Section: Multimodal Methodsmentioning
confidence: 99%
“…7D (iii)) graphene in devising GR-enhanced spectro-electrochemical sensors (GE-SPECSs). 195 Their studies revealed that hole-doped h-graphene exhibited superior GERS signals compared to pgraphene, achieving a LOD of around 10 −7 M. By capitalizing on the adjustable work function of graphene, they demonstrated the ability to modulate the GERS signal and probe various oxidation states of molecules through the application of appropriate external potentials (Fig. 7D (i)).…”
Section: Multimodal Methodsmentioning
confidence: 99%
“…[ 2–8 ] Due to the aforementioned properties and extreme sensitivity to the environment, monolayers of layered materials can be used in wide ranging applications such as ultra‐high performance optoelectronics, sensors, flexible electronics, energy conversion and storage, biomedicine, and defense. [ 9–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Due to the aforementioned properties and extreme sensitivity to the environment, monolayers of layered materials can be used in wide ranging applications such as ultra-high performance optoelectronics, sensors, flexible electronics, energy conversion and storage, biomedicine, and defense. [9][10][11][12][13][14][15] At a laboratory level, preparation of monolayers (1L) of 2D materials is straightforward as small individual flakes on the order of tens of μm in lateral size usually suffice. However, the utility of 2D materials at an industrial level is still limited by the conflicting relation between the size and quality of 1L flakes.…”
Section: Introductionmentioning
confidence: 99%